Highlight article: Effects of tocotrienol supplementation in Friedreich's ataxia: A model of oxidative stress pathology. Issue 3 (February 2020) - Bolotta, Alessandra; Pini, Antonella; Abruzzo, Provvidenza M; Ghezzo, Alessandro; Modesti, Alessandra; Gamberi, Tania; Ferreri, Carla; Bugamelli, Francesca; Fortuna, Filippo; Vertuani, Silvia; Manfredini, Stefano; Zucchini, Cinzia; et al.
Friedreich's ataxia is an autosomal recessive disorder characterized by impaired mitochondrial function, resulting in oxidative stress. In this study, we aimed at evaluating whether tocotrienol, a phytonutrient that diffuses easily in tissues with saturated fatty layers, could complement the current treatment with idebenone, a quinone analogue with antioxidant properties. Five young Friedreich's ataxia patients received a low-dose tocotrienol supplementation (5 mg/kg/day), while not discontinuing idebenone treatment. Several oxidative stress markers and biological parameters related to oxidative stress were evaluated at the time of initiation of treatment and 2 and 12 months post-treatment. Some oxidative stress-related parameters and some inflammation indices were altered in Friedreich's ataxia patients taking idebenone alone and tended to be normal values following tocotrienol supplementation; likewise, a cardiac magnetic resonance study showed some improvement following one-year tocotrienol treatment. The pathway by which tocotrienol affects the Nrf2 modulation of hepcidin gene expression, a peptide involved in iron handling and in inflammatory responses, is viewed in the light of the disruption of the iron intracellular distribution and of the Nrf2 anergy characterizing Friedreich's ataxia. This research provides a suitable model to analyze the efficacy of therapeutic strategies able to counteract the excess free radicals in Friedreich's ataxia, and paves the way to long-term clinical studies. Impact statement: Oxidative stress is involved in the pathogenesis of Friedreich's ataxia (FRDA), a genetic disorder causing neurodegeneration due to the dramatic reduction in the expression of frataxin. To date, no cure is available for FRDA patients. In some countries, FRDA patients assume idebenone in order to counteract the effects of frataxin deficiency. We demonstrate that idebenone treatment alone is not able to abrogate oxidative stress in FRDA patients, whereas the combined treatment with tocotrienols might be more efficient and perhaps produce clinical improvement. In fact, a decrease in oxidative stress and inflammation markers can be seen after two months and is more pronounced after one year of treatment. This is, in our opinion, valuable information for clinicians, since idebenone is the treatment of choice for FRDA patients in some countries.